Study of the reaction mechanism of the transesterification of triglycerides catalyzed by zinc carboxylates - Reinoso, Deborath Mariana (2013)
In this theoretical and experimental study, the mechanisms for the transesterification of triglycerides catalyzed by zinc carboxylates were analyzed and discussed. Different alternatives were examined: (A) the classic Lewis acid mechanism involving the coordination of the triglyceride through the carbonyl group with the Zn2+ ion, (B) the coordination of methanol with the Zn2+ followed by carboxylate shift, and (C) the co-coordination of methanol and the triglyceride with the Zn2+ ion. The preferred mechanism included the initial coordination of methanol, carboxylate shift and the co-coordination of the triglyceride with an alkoxide-like moiety. The fatty acid esterification reaction catalyzed by zinc carboxylates was also studied. The anion exchange between the carboxylate in the Zn salt and the fatty acid to be esterified was analyzed.